Application Development in iOS 7. - Begeman, Kyle (Packt Publishing, 2014)
In Detail Unleash the new features of iOS 7 within the latest Xcode development environment. One of the most important pieces of any SDK is the Integrated Development Environment (IDE), which is why we will start by learning all the new features of Xcode 5. Moreover, we will get to know what's new in Foundation Framework, one of the building blocks of iOS development. We then move on to exploring the new and improved Auto Layout, a feature that was previously plagued by quite a few issues and shunned by many developers. Next, we will start building our application from scratch while applying our new knowledge of the IDE. Also, we will make use of the newly introduced TextKit to make our text more dynamic in nature. Finally, we will utilize the UI Kit Dynamics to give our application some flair. This book is a practical breakdown of all the new iOS 7 features for developers. Approach A hybrid between informative overview and step-by-step instruction, this book is the ultimate guide to iOS 7 application development. Who this book is for If you are an iOS developer who is looking to understand the new features within iOS 7 and Xcode 5, then this book is for you. In order to fully understand the concepts in this book, it is recommended you have at least some experience with previous versions of iOS.